1998
DOI: 10.1021/es970419y
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon Contamination in Marine Sediments near Kitimat, British Columbia

Abstract: Polycyclic aromatic hydrocarbons (PAHs), like many other hydrophobic organic contaminants, are rapidly sorbed to particles and incorporated within sediments in aquatic systems. The PAH composition within the sediments reflects the source(s) from which the PAHs were derived. However the "source signature" may be altered by postdepositional weathering or biodegradation. In the present study, variation in PAH composition was investigated in size-fractionated sediments and depth-fractionated sediments collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…Concentration, structure, and the type of organic matter influence pollutant distribution in soil and sediments. Higher concentrations of pollutants usually exist in sediments with higher concentration of organic matter (Simpson et al 1998;Kleineidam et al 1999;Rockne et al 2002) but statistically significant relationship was not found in these studies. A weak relationship was observed between PAHs and total organic carbon (TOC) with correlation coefficient of R ranging from 0.46 to 0.82 in background soils from Norway (Nam et al 2008).…”
Section: Introductioncontrasting
confidence: 65%
“…Concentration, structure, and the type of organic matter influence pollutant distribution in soil and sediments. Higher concentrations of pollutants usually exist in sediments with higher concentration of organic matter (Simpson et al 1998;Kleineidam et al 1999;Rockne et al 2002) but statistically significant relationship was not found in these studies. A weak relationship was observed between PAHs and total organic carbon (TOC) with correlation coefficient of R ranging from 0.46 to 0.82 in background soils from Norway (Nam et al 2008).…”
Section: Introductioncontrasting
confidence: 65%
“…On the other hand, volatile PAHs (3 rings) tend to distribute not only in the (fine) aerosol particles, but also in (coarse) runoff particles (Hoffman et al, 1984;Lee et al, 2005;Takada et al, 1990;Venkataraman et al, 1999). Consistently, Simpson et al (1998) and Oen et al, (2006) pointed out that less volatile PAHs tend to be enriched in fine particles while volatile PAHs tend to distribute in coarse particles in coastal sediment.…”
Section: Seasonal Variation Mechanisms Of the Fluxes Of Pahsmentioning
confidence: 74%
“…Besides, black carbon (BC) also benefited PAHs deposition within the sediments (Bucheli et al 2004;Oen et al 2006;Agarwal and Bucheli 2011). The grain size was also considered as an important factor influencing PAHs deposition and adsorption/desorption within the sediments (Simpson et al 1998;Wang et al 2001;Thorsen et al 2004). PAHs were easier to be absorbed on particles with small size rather than large ones (Kukkonen and Landrum 1996;Wu et al 2006;Zhao et al 2012).…”
Section: Relationships Among Pahs Toc and Grain Sizementioning
confidence: 99%